Percepción social de los hombres en condición de desplazamiento forzado de la población de San Pablo Bolívar hacia la violencia de género contra la mujer (2017)
Violence against women especially exercised by their partner and sexual violence is a serious public health problem and a violation of human rights of women therefore this paper what is sought is to know the social perception of man towards gender violence against women in the population of San Pablo Bolivar , for this quantitative research " this study includes the description , recording, analysis and interpretation of the current nature and composition of processes phenomenon is made the gender-based violence against women , specifying their characteristics and relevant features , and non-experimental since it is performed without deliberately manipulate variables , where he chose a population of 80 men between ages ranges from 20 to 70 years..